Theoretical and experimental investigation on surface segregation of Cu-Ni(S) bulk and thin film alloys - Yan, Xin Liang (University of the Free State, 2017)
In this study, the surface segregation in a Ni-Cu alloywasinvestigated by modeling the segregation process theoreticallyand also measuring it experimentally. This was performedfor abulkcrystaland thin films. In addition to the segregation measurements, the Ni/Cumultilayer thin films werealso used to study the interdiffusion of Cu and Ni with AES depth profiling.TheMRI model was used toquantitatively evaluate the sputtering-induced surface roughness and depth resolution for AES and SIMS depthprofiling. Depth profiles ofthe Ni/Cu polycrystalline multilayer thin films were performedby AES and SIMSin combination with ion sputtering. The measured depth profiles data were quantitative analyzed with the MRI model. The sputtering-induced surface roughness and depth resolutionwere evaluatefor sputtering with (i) a stationary sample, (ii) a rotating sample and (iii)a stationary sample with two ion beams simultaneously. The results showthat the depth resolution is smaller when profiling with dual-ion beam vs. a single-ion beam. It was also found that profiling with a lower ion energy result in a better (smaller) depth resolution. Rotation of the sample during ion sputtering had the better (smaller) depth resolution. Depth profiling with Cs+ ion sputtering had the best depth resolution compared to Xe+ and O2+ ion sputtering. The MRI model was also used for extracting the interdiffusion coefficients for the AES depth profiles of a Ni/Cumultilayer. The interdiffusion parameter for Cu/Ni multilayer thin films was characterized for the first interface Do =6.2×10-13 m2/s and Q =101.4 kJ/mol, and the last Cu/Ni interface Do=6.3×10-14 m2/s and Q =79.0 kJ/mol. It was clearly showing that the depth-dependent interdiffusion coefficients are depth-dependent. The segregation of Cu and S from a ternary Ni-Cu(S) bulk alloy was measured with AES using linear temperature programmed heating and constant temperature heating. The segregation data were fitted with the modified Darken model and the segregation parameters were DoCu in Ni = 8.6×10-14 m2/s, QCu in Ni = 145.2 kJ/mol, DoS in Ni = 9.2×10-2 m2/s, QS in Ni = 224.0 kJ/mol, ΔGCu = -36.0 kJ/mol, ΔGs = -136.0 kJ/mol, ΩCu-Ni = 7.6 kJ/mol, ΩS-Ni = 28.1 kJ/mol and ΩCu-S = -10.3 kJ/mol. The segregationsof Cu from a Ni-Cu thin film alloy were measured using AES with linear temperature programmed heating. The segregation measured profile data were fitted with a modified Fick’s model and the segregation parameters obtained Do= 2.8×10-13m2/s and Q= 135.3kJ/mol for the 26nm thin film and for thicker film (52nm) Do= 2.9×10-13m2/s and Q= 140.5 kJ/mol. The modified Darken model is there adapted to simulate segregation from thin films and also showed that the thickness of the thin film significantly affects the segregation.
Thesis (Ph.D. (Physics))--University of the Free State, 2017
Keywords: Surface segregation; Ni-Cu alloy thin films; Interdiffusion; Ni/Cu multilayer thin films; Modified darken model; MRI model; Ni-Cu(S); AES depth profile; Tof-sims depth profile; Depth resolution; Sputtering induced roughness; Segregation energy; Interaction energy; Ternary alloy system; Thin films; Alloys